An Odd Solution – Comments on the Margins of a Recent Debate on National Minority Suffrage: ECtHR judgement in Case Bakirdzi and E.C. v. Hungary - Sándor-Szalay, Elisabeth; Kiss, Balázs (Pécs journal of international and European law, 2023)
This case note analyses the judgment of the European Court of Human Rights in the case of Bakirdzi and E.C. v. Hungary. The judgment pertains to the effective participation of minorities in public affairs in the context of electoral rights. In its ruling, the ECtHR found a violation of Article 3 of the First Additional Protocol to the ECHR, read alone and in conjunction with Article 14 of the Convention. The judgment underlines important principles as to preferential arrangements regarding the participation of national minorities in the electoral process.